The leading role of West Siberian Research and Geological Oil Exploration Institute in the development of the oil and gas potential of the West Siberian oil and gas province and the development of the country’s mineral resource base - V. N. Borodkin; M. V. Komgort; I. I. Nesterov (Georesursy, 2024)
The history of creation is given, the complex of studies carried out by the Tyumen branch of Siberian Research Institute of Geology, Geophysics and Mineral Resources (SNIIGGiMS) in 1960–1964 and by West Siberian Research and Geological Prospecting Oil Institute (ZapSibNIGNI) in 1964–1996 is analyzed. The role of the Institute in the substantiation of oil and gas potential and developing the resource base of the West Siberian oil and gas province is shown. The scientific forecasts and developments of the Institute’s employees, which influenced the increase in the efficiency of geological exploration are presented. In preparing the article, previously unpublished documents from the archive of the Directorate of ZapSibNIGNI were used.